Diet in Brain Health and Neurological Disorders: Risk Factors and Treatments - Brandt, Jason (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The role of nutrition in health and disease has been appreciated from time immemorial. Around 400 B.C., Hippocrates wrote "Let food by thy medicine and medicine be thy food." In the 12th century, the great philosopher and physician Moses Maimonides wrote "any disease that can be treated by diet should be treated by no other means." Now, in the 21st century, we are bombarded by claims in the media of "superfoods," wondrous nutritional supplements, and special diets that promise to cure or prevent disease, improve health and restore functioning. Much of the focus has been on neurological disease, brain health and psychological functioning (behavior, cognition, and emotion). The hyperbole aside, there has been considerable progress in the past decade in our understanding of the contribution of specific nutrients and dietary patterns to brain development, physiology, and functioning. This Special Issue of Brain Sciences is devoted to the latest research on the role of nutritional deficiencies and excesses in the genesis of brain dysfunction, and use of diet for the prevention and treatment of brain and mental disorders. Basic laboratory and clinical research studies of the immature, adult, and aged nervous system are all welcome.